The linguistics of orality: a psycholinguistic approach to private and public performance of classical Attic prose - Vatri, A (2013)
The thesis tests the hypothesis that certain aspects of linguistic variation in Attic prose are related to the type of oral performance, private or public, which the author envisaged for his text. This hypothesis rests on the assumption that authors more or less consciously optimized their texts for their intended communicative situation. A crucial feature of texts optimized for public delivery was clarity, which figures as an essential component of the 'virtue of speech' in the Greek rhetorical thought. In private situations the audience itself could alter the pace of reading or recitation. Clarifications could be sought, and pauses and repetitions would be possible. The case was different with public situations, where the text itself coincided with its performance and it was entirely up to the speaker to determine the way in which the audience would access it. Especially in political and judicial contexts, where important decisions were to be made, public speakers could not afford being unclear. In order to test whether public texts were clearer than private texts, 'clarity' must be defined in a linguistically thorough way. Modern psycholinguistics studies human language comprehension, and experimental research has revealed language-independent mechanisms which can be confidently applied to dead languages. In the thesis, clarity is measured by the number of syntactic, semantic, and referential reanalyses which linguistics structures induce in a given amount of text. This methodology is tested on a corpus of Attic speeches, which includes both texts that were devised exclusively for written circulation and private delivery, and texts that were at least conceived for public delivery, although we do not know to what extent they correspond to the versions which were actually delivered. The difference between the average score of 'public texts' and that of 'private texts' is statistically significant and supports the hypothesis that 'public texts' were generally clearer than 'private texts' for audiences of native speakers.